THE INFLUENCE OF FINANCIAL LITERACY AND THE AMOUNT OF POCKET MONEY ON CONSUMPTION BEHAVIOR THROUGH LIFESTYLE OF ECONOMIC EDUCATION STUDENTS OF UNIVERSITAS PGRI MPU SINDOK - Palupi, Ragil Retno; Kurnia Dewa, Angga Gama; Herna Pambayun, Mochammad Bima; Fikri Muzakki, M. Alfian (Sekolah tinggi ilmu ekonomi pemuda, 2025)
In the current Gen Z era, the majority of college students prefer to purchase products online rather than offline, as online purchases are more affordable than offline purchases. Given this phenomenon, researchers are interested in delving deeper into analyzing the influence of financial literacy and pocket money on consumer behavior, with lifestyle as a mediating variable, on economics education students at Universitas PGRI MPU Sindok. This study used a quantitative approach. This research was conducted in the Economics Education Study Program at Universitas PGRI MPU Sindok, with a population of 146 students in semesters 1, 3, 5, and 7. The sample size of this study was 20 students selected through proportional sampling using the Slovin formula with a 5% error rate. The data collection technique used a questionnaire. The data analysis technique used the SEM-PLS test with the help of the SmartPLS 4.0.9.2 software program. The results of the study were 1) Financial literacy has a positive and insignificant effect on consumption behavior, 2) Financial literacy has a positive and significant effect on lifestyle, 3) The amount of pocket money has a positive and insignificant effect on consumption behavior, 4) The amount of pocket money has a positive and significant effect on lifestyle, 5) Lifestyle has a positive and insignificant effect on consumption behavior, 6) Financial literacy has a positive and insignificant effect on consumption behavior through lifestyle, 7) The amount of pocket money has a positive and insignificant effect on consumption behavior through lifestyle. A limitation of this study is that there were only two independent variables used to measure students' entrepreneurial interest: financial literacy and pocket money. Therefore, future research is expected to add other independent variables not included in this study. The population used was only students majoring in Economics at Universitas PGRI MPU Sindok. Therefore, future research is expected to reach students beyond Universitas PGRI MPU Sindok.